Garfield Full Course Volume One - Davis, Jim 1945; Evanier, Mark; Nickel, Scott; Barker, Gary; Davis, Dan W.; De Carlo, Mike; Hirsch, Andy, 1987-; Heike, Mark; Heike, Stephanie; Lamb, Braden; Moore, Lisa (Colorist); Wands, Steve (Los Angeles, CA KaBOOM!, 2023)
"Just in time for his 45th anniversary, Garfield returns in the first volume of a redesigned and updated collection! Join Garfield as he begins his comic book exploits with Jon, Odie, and the rest of the gang in this all-ages must-read series guaranteed to bring you all the laughs (and lasagna) you can handle. Along the way Garfield and the gang meet many new friends, including a mouse that wants to be a cat (and sometimes a dog), a mummy, and Pet Force! Yes, we're going to Planet Dorkon to hang out with the galaxy's greatest superheroes. Writers Mark Evanier (The Garfield Show) and Scott Nickel, artists Gary Barker, Dan Davis, Mike DeCarlo, Andy Hirsch, and Mark & Stephanie Heike, bring creator Jim Davis' iconic character back for new and old fans alike in this first of six value-priced collections! Collects Garfield #1-8."--Amazon.com.
"Originally published in single magazine form as Garfield no. 1-8."
112759
Keywords: Garfield -- (Fictitious character) -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Pets -- Comic books, strips, etc; Pet owners -- Comic books, strips, etc; Humorous comics; Funny animal comics; Graphic novels; Comics (Graphic works)